Recent advances in cocoa chemistry and roasting - Konar, Nevzat; Palabiyik, Ibrahim; Karimidastjerd, Atefeh; Toker, Omer Said; Gorgulu, Ahmet (ELSEVIER SCIENCE LONDON, 2025)
Background: Although cocoa roasting has been a process used for many years, research continues due to the lack of standardization and various issues. These studies focus on the interaction between roasting methods and conditions with cocoa chemistry. However, reviews on cocoa chemistry and roasting are limited. In recent years, the development of cocoa alternatives triggered by fluctuations in cocoa supply has increased the importance of the relationship between cocoa chemistry and technological processes. Scope and approach: The scope of this review focuses on the relationship and interaction between cocoa chemistry and roasting. In this context, the roasting process of cocoa (beans, nibs, and liquor) has been discussed, considering its relationship with the chemical composition elements that are the primary motivation for cocoa consumption (flavor precursors, volatile and non-volatile flavor compounds, organic acids) and potential chemical food safety risks (acrylamide, biogenic amines, polycyclic aromatic hydrocarbons), based on recent studies and findings. Additionally, approaches that can be used to monitor and assess cocoa roasting have been addressed in terms of cocoa chemistry, highlighting priority research and study areas. Key findings and conclusions: Roasting significantly influences cocoa's flavor and chemical profile. Innovation in roasting technology like microwave, superheated steam roasting and refiner-conche systems could aim to enhance flavor, maintain food safety, and improve efficiency. Future research on balancing optimal flavor with reduced risks, such as acrylamide, polycyclic aromatic hydrocarbons and other harmful components, and also AI-driven systems for dynamic optimization sustainable cocoa processing can be considered.
Keywords: Chocolate; cocoa; Flavor; Food safety; roasting; GEOBACILLUS-STEAROTHERMOPHILUS; ANTIOXIDANT ACTIVITY; PEPTIDE PRECURSORS; VOLATILE FLAVOR; DARK CHOCOLATE; BEANS; PRODUCTS; QUALITY; TIME; OLIGOPEPTIDES; Food Science & Technology